A Profile of Occupational Therapists Working in School-Based Practice in Australian Primary Schools - Jill Jeremy; Ilektra Spandagou; Joanne Hinitt (Occupational Therapy International)
Inclusive education has increased the demand for school-based occupational therapy services and has reconceptualised the practice in mainstream schools. Therapists are now expected to work collaboratively with teachers within tiered intervention models to support access and participation of all students, including those with disabilities, within the natural classroom context. School-based occupational therapy has become a specialised area of practice, as therapists work within educational, rather than health, systems and processes. While the growth in demand and expanded scope of practice is positive for the profession, predicted workforce shortages and the necessity for specialised and enhanced practice present significant challenges. The ability of the profession to fully support the demands of an inclusive education system remains unclear. As accurate, up-to-date information on the school-based therapy workforce is the foundation for planning future personnel needs, knowledge of the current state of the workforce is critical. There is a paucity of national data regarding this growing area of practice. The aim of this study is to describe a current profile of school-based occupational therapists to better understand the workforce, practice patterns, and the funding landscape in Australia. A convenient and purposive sample of 108 Australian paediatric occupational therapists working in mainstream primary schools in New South Wales, Queensland, and Victoria was surveyed in this quantitative study, which was analysed using descriptive statistics. Results provide some insights into the workforce and practice of school-based therapy in Australia offering preliminary data for future planning in this important and growing area of paediatric practice. While specific to the local context, results invite cross-national and global comparison to reveal universal trends and localised nuances across diverse settings.